Household Bundling of Health Insurance - Nguyen, Anh (The Review of Economics and Statistics, 2025)
This paper examines how to bundle household health insurance, treating each member’s policy as a product in the bundle. Two regimes are analyzed: pure bundling and bundle discounts. Pure bundling is socially optimal when willingness to pay differs across members, when the bundle is valued more than individual components, or when households prefer insuring costlier members, implying within-household adverse selection. Using Vietnam’s Social Health Insurance data, structural estimates show substantial heterogeneity in willingness to pay, driven mainly by health-type differences. A pure bundling policy increases consumer surplus by 43% relative to bundle discounts.